Low-voltage blue-phase liquid crystal display with single-penetration electrodes. Issue 14 (8th December 2017) - Guo, Yuqiang; Fu, Mingzhu; Ren, Yaxuan; Wang, Yifei; Mu, Qihui; Ma, Hongmei; Zhu, Jiliang; Sun, Yubao
ABSTRACT: A blue-phase liquid crystal display (BPLCD) with single–penetration (S-P) electrodes is proposed to reduce the operating voltage. X-shape inclined-electric field is induced by the S-P electrodes with 2 3 μm height, which can lower the operating voltage by 45%, and improve the transmittance compared with BPLCD with conventional in-plane electrodes. Moreover, the wide viewing angle and very small image distortion index can be obtained in this structure with a half-wave biaxial film. The proposed structure shows simple etching control and easy one-drop filling process of blue-phase liquid crystal compared with dual-convex-penetration electrodes. GRAPHICAL ABSTRACT: